Effet Du Fumier Sur Le Bilan Des Éléments Nutritifs Des Champs Dans Le Terroir De La Néma Au Saloum (Sénégal) - Coly, Ismaïla; Diop, Babacar; Goudiaby, Arfang Ousmane Kémo (European Scientific Journal, ESJ, 2018)
In the land of Nema, fields show low agricultural potential due to high human and climatic pressure. To increase their agricultural production, the populations have opted either for the use of chemical fertilizer or for the supply of manure through the Agriculture-Livestock integration. This paper focuses on evaluating the effect of on-farm use of manure on groundnut pod and groundnut production, and nutrient balance at the field level. 20 square plots of 2m each were used per field on the monitored farms. The hay and pod samples were taken therein, weighed, and dried in an oven at 60° C to a constant weight. This work was carried out for both fertilized fields and unfertilized fields (controls). In these same farms, samples of manure produced were collected and analyzed. The production of peanut and groundnut pods in the fertilized fields and in the control fields shows an overall positive effect of the manure on the yields in the land of the Néma. Taking into account the figures of the average deficits, the nitrogen, phosphorus, and potassium balance is deficient in ground-level groundnut peanut fields. This is due to the low manure doses per hectare and its low nutrient content.